Utilization of Concrete Services in Child Welfare: A Mixed Method Analysis of a Title IV-E Waiver Demonstration Program. Issue 2 (15th March 2018) - Pierce, Barbara; Jaggers, Jeremiah W.; Bloomquist, Kori; Imburgia, Teresa M.; Danh, Marie; Hall, James
ABSTRACT: Concrete services are goods and services, such as rent, utilities, healthcare, or other tangible services, that are purchased directly by child welfare agencies to help support the short-term needs of a family. Practice wisdom in social work details the importance of meeting basic needs in order for clients to be able to concentrate on completing the case plan. Some literature has mentioned the importance of concrete services for child welfare practice. However, research has been limited about utilization of these services and their impact on child welfare outcomes. The current mixed methods study examines expenditures for concrete services across four categories over a four-year period in one Midwestern state. The justifications for caseworker concrete service requests and the perceptions of regional and executive managers regarding the effectiveness of the use of concrete services are also examined. Descriptive analysis revealed distributions varied by age and concrete service type. Both caseworker justifications and regional manager interviews revealed the same general themes for children: support of child safety, permanency, and well-being are supported with the use of concrete services.